The Use Of Ultraviolet In The Production Of Nursing Tilapia Fish Oreochromis niloticus Using A Recirculation System - Antika, Rendi; Cokrowati, Nunik; Scabra, Andre Rachmat (Program Studi Budidaya Perairan Universitas Mataram, 2024)
The need for tilapia fish supplies for the world market is not yet fully met, so the implementation of intensive cultivation is expected to increase aquaculture production results. Recirculation systems are an option for controlling the quality of cultivation water, and the addition of UV lights is expected to be able to kill bacteria found in cultivation waters. This research aims to evaluate the use of UV lamps in fish nurseries and analyze the best use of UV lamps in tilapia nurseries. This research was carried out for 45 days, at the Fish Production and Reproduction Laboratory, Mataram University using an experimental method with a completely randomized design (RAL) consisting of 4 treatments and 3 replications, namely P1: without UV lamp, P2: 5 Watt, P3: 10 Watts, and P4: 15 Watts. Test parameters include absolute length growth rate, specific length, absolute weight, specific weight, Feed Conversion Ratio (FCR), Survival Rate (SR), water quality and bacterial abundance. Data were analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test. The results showed that the best growth rate parameters, Feed Conversion Ratio (FCR), Survival Rate (SR) and bacterial abundance were found in P4 with an absolute length growth rate of 6.4cm, specific length of 0.05%/day, absolute weight growth of 9.7gr, specific weight of 0.06%/day, Feed Conversion Ratio (FCR) value of 0.7, Survival Rate (SR) of 94% and bacterial abundance of 5.7 x 105 CFU/ml.